The Use of Cue Cards In Teaching Procedure Text To Promote Seventh Graders’ Writing Skills - Ersih Lesnussa; Dessy Dwi Yudha Santhi; Lidwina Sri Ardiasih (Edumaspul: Jurnal Pendidikan, 2024)
The curriculum has recommended several teaching pedagogies implemented in the classroom to make it easier for students to achieve learning One of the aims is to use cue cards to increase awareness of specific areas of interest in a tolerant, non-threatening environment; So, in this case In this case, the researcher stated that the cue card was assumed to be a method applied in teaching writing in one of the junior high schools in my shame. Using a qualitative research design, this research involves a class of 30 junior high school students in rural Maluku. Based on the data analysis and hypothesis testing carried out in this study, the following result can be drawn, In connection with the first research question regarding the application of cue card media to make it easier for students to compose procedural texts, it can be concluded that students complete the task well when they complete their practice in carrying out the stages of learning to write a procedure text. They complete the steps: introduction, main activities, and closing activities. In the second research question, Students' difficulties found during the learning process when cue cards are used in their classroom, the students’ said Writing is the most difficult problem in learning English faced by students during the teaching and learning process in class. Several students said that using cue cards in learning felt difficult. The third research question, Cue Cards, allows students to increase their vocabulary in the process of writing a text in English.